An Empirical Study on the Utility of Sharpe's Single Index Model in Optimal Portfolio Construction - Nalini, R. (Indian Journal of Finance, 2014)
While investors take investment decisions, they expect high returns at minimum risk, and they also do not want to block their entire investment in a single security. So, they aim at creating optimal portfolios through diversification. The present study examined the impact of a single market index on the different companies' stocks included in the index. By using Sharpe's single index model (SIM), analysis of risk and return is made easy. The study aimed at applying Sharpe's single index model for constructing an optimal portfolio and understanding the effect of diversification of investments. The study is empirical in nature and is based on secondary data. All the 30 companies listed in the BSE were included in the study. Sensex was used as the benchmark index. Data for a 7- year period (2005-2012) were used for portfolio construction. The study showed that by using this model, the investors can minimize their overall risk and maximize the returns over any period of time. It was found that even companies with high rates of return were not included in the portfolio as the risk involved in such companies was high. It was also proved that SIM has been useful to create an optimal portfolio by diversifying almost all the unsystematic risks.